Genetic Architecture of MAPT Gene Region in Parkinson Disease Subtypes - Pascale, Esterina; Di Battista, Maria Elena; Rubino, Alfonso; Purcaro, Carlo; Valente, Marcella; Fattapposta, Francesco; Ferraguti, Giampiero; Meco, Giuseppe (Frontiers in Cellular Neuroscience, 2016)
The microtubule-associated protein tau (MAPT) region has been conceptualized as a model of the interaction between genetics and functional disease outcomes in neurodegenerative disorders, such as Parkinson disease. Indeed, haplotype-specific differences in expression and alternative splicing of MAPT transcripts affect cellular functions at different levels, increasing susceptibility to a range of neurodegenerative processes. In order to evaluate a possible link between MAPT variants, PD risk and PD motor phenotype, we analyzed the genetic architecture of MAPT in a cohort of PD patients. We observed a statistically significant association between the H1 haplotype and PD risk (79.5 vs 69.5%; 2 =9.9; OR,1.7; 95% CI, 1.2-2.4; p=0.002). The effect was more evident in non tremor dominant PD subjects (NTD-PD) (82 vs 69.5%; 2 =13.6; OR, 2.03; 95% CI, 1.4-3; p=0.0003), while no difference emerged between PD subgroup of tremor dominant patients (TD-PD) and control subjects. Examination of specific intra-H1 variations showed that the H1h subhaplotype was overrepresented in NTD-PD patients compared with controls (p=0.007, OR 2.9; 95%CI 1.3-6.3). Although we cannot exclude that MAPT variation may be associated with ethnicity, our results may support the hypothesis that MAPT H1 clade and a specific H1 subhaplotype influence the risk of PD and modulate the clinical expression of the disease, including motor phenotype.